2017
DOI: 10.1002/mus.25723
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided hydrodissection decreases gliding resistance of the median nerve within the carpal tunnel

Abstract: Introduction: The aim of this study was to assess alterations in median nerve (MN) biomechanics within the carpal tunnel resulting from ultrasound-guided hydrodissection in a cadaveric model. Methods: Twelve fresh frozen human cadaver hands were used. MN gliding resistance was measured at baseline and posthydrodissection, by pulling the nerve proximally and then returning it to the origin. Six specimens were treated with hydrodissection, and 6 were used as controls. Results: In the hydrodissection group there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 32 publications
0
42
0
Order By: Relevance
“…Additionally, ultrasound guidance was used in the two trials of D5W, but not in all studies using PRP. A cadaveric study has demonstrated that a bolus saline injection could effectively reduce the peak gliding resistance of the median nerve [46]. Another randomized controlled trial pointed out that precise hydro-dissection of the median nerve using saline under ultrasound guidance yielded better clinical outcomes than subcutaneous saline injection [47].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ultrasound guidance was used in the two trials of D5W, but not in all studies using PRP. A cadaveric study has demonstrated that a bolus saline injection could effectively reduce the peak gliding resistance of the median nerve [46]. Another randomized controlled trial pointed out that precise hydro-dissection of the median nerve using saline under ultrasound guidance yielded better clinical outcomes than subcutaneous saline injection [47].…”
Section: Discussionmentioning
confidence: 99%
“…5,12 Advantages of the procedure are that injection may be applied using sterile saline solution or physiologically similar fluid and it may be performed in office conditions. 13 Rosales et al have applied a perisciatic USguided infiltration technique. 14 They used a mixture containing 20 mL saline, 4 mL local anaesthetic and 1 mL corticosteroid and infiltrated in the perisciatic region between the gluteus maximus and pelvitrochanteric muscles.…”
Section: Discussionmentioning
confidence: 99%
“…In this procedure, a large (15 ml or less) volume of anesthetic, saline, or dextrose‐containing fluid is injected in the perineural region in hopes of breaking adhesions that may be contributing to the mononeuropathy. Hydrodissection (or hydroneurolysis) has been shown to reduce gliding resistance in the carpal tunnel in cadaver models . This technique may be especially helpful in situations where scar tissue contributes to the pathology, such as in recurrent carpal tunnel syndrome (CTS) after a surgical release .…”
Section: Types Of Ultrasound‐guided Interventionsmentioning
confidence: 99%
“…Studies have demonstrated reduced nerve mobility in CTS, and histopathology has demonstrated increased activity of fibroblasts in the subsynovium, which results in adhesions . Mechanical hydrodissection may relieve these adhesions and is far easier to perform using an in‐plane transverse approach. In addition to the injection, operators can repeatedly fenestrate or “release” the transverse carpal ligament with a needle, or perform a minimally invasive release with a specialized surgical instrument …”
Section: Approach To Ultrasound‐guided Treatment Of Individual Entrapmentioning
confidence: 99%